CFD NUMERICAL ANALYSIS OF A PROPOSED CHANGE IN THE CHANNEL GEOMETRY DOWNSTREAM OF A REVERSED TAINTER GATE - Corte, M. D.; Oliveski, R. C.; Marques, M. G.; Dai Pra, M. (Revista de Engenharia Térmica, 2015)
Reversed Tainter gates are often used to control flow in the filling and emptying locks navigation systems of high fall. High speeds and pressure fluctuations may occur in the flow downstream of these gates, the flow cavitation may occur, damaging the structure. One way proposed to mitigate this problem is through geometric changes in the channel downstream of the gate. In this study was analyzed using CFD the effect of an expansion in the roof and the base of the conduit, followed by a straight section and a subsequent contraction until returning to the original geometry. It was observed that the pressure at the base of the conduit increases with the modification, however peaks of positive and negative pressures occur due to the shape change of the geometry of the corners not be smooth. The size of recirculation downstream of the gate increases with the geometrical alteration, increasing the distance required for pressure recovery.